2023
DOI: 10.1080/07853890.2023.2269558
|View full text |Cite
|
Sign up to set email alerts
|

TREM-1, TREM-2 and their association with disease severity in patients with COVID-19

Ruyue Fan,
Zuowang Cheng,
Zhisheng Huang
et al.

Abstract: Background Delayed diagnosis and inadequate treatment caused by limited biomarkers are associated with the outcomes of COVID-19 patients. It is necessary to identify other promising biomarkers and candidate targets for defining dysregulated inflammatory states. Methods The triggering receptors expressed on myeloid cell (TREM)-1 and TREM-2 expression from hospitalized COVID-19 patients were characterized using ELISA and flow cytometry, respectively. Their correlation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In a recent study, the area under the ROC curve (AUC) for sTREM-1 in predicting severe COVID-19 was reported as 0.656, but the optimal cut-off value and its predictive value for prognosis were not specified. 35 However, a study has indicated that sTREM-1 has high predictive value for severe COVID-19, with an AUC of 0.96 (95% CI: 0.94–0.98). 36 Regarding prognosis, an earlier study involving 76 COVID-19 patients found that sTREM-1 had an AUC of 0.86 (95% CI: 0.77–0.95) for predicting intubation/death at 30 days, with an optimal cut-off value of 689 pg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the area under the ROC curve (AUC) for sTREM-1 in predicting severe COVID-19 was reported as 0.656, but the optimal cut-off value and its predictive value for prognosis were not specified. 35 However, a study has indicated that sTREM-1 has high predictive value for severe COVID-19, with an AUC of 0.96 (95% CI: 0.94–0.98). 36 Regarding prognosis, an earlier study involving 76 COVID-19 patients found that sTREM-1 had an AUC of 0.86 (95% CI: 0.77–0.95) for predicting intubation/death at 30 days, with an optimal cut-off value of 689 pg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our findings suggested that Trem2 participated in the clearance of Pneumocystis . An emerging role for Trem2 in regulating immune functions of macrophages in infectious diseases, including bacterial, viral, and parasitic infections [ 32 34 ]. In mycobacterial infections, Lizasa et al indicated that Trem2 suppressed the activation of macrophages and ultimately lead to mycobacterial evasion of host immunity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%